Essa gente lá de fora - José Alves Sobrinho (Estudos de Literatura Brasileira Contemporânea)
In an unpublished poem, dedicated to Joseilda de Sousa Diniz, the author discusses the difficult relationship between popular poets and academical researchers. Alongside with other interlocutors already engaged in building new ways of thinking this artisitic production, the poet foresees the possibility of establishing another universe of exchanges.